A simple method for preparing ultra-light graphene aerogel for rapid removal of U(VI) from aqueous solution. (August 2019) - Zhao, Donglin; Wang, Yangyang; Zhao, Siyu; Wakeel, Muhammad; Wang, Zheng; Shaikh, Rehan S.; Hayat, Tasawar; Chen, Changlun
Abstract: In this study, graphene aerogel (GA) was successfully prepared through a simple hydrothermal method. The resulting GA exhibited a porous network structure with a large specific surface area (350.8 m 2 /g), ultra-light mass and easy separation from water. The pHIEP value of the GA was estimated to be 3.5. The adsorption process and the factors that affect adsorption capacity were studied. The adsorption could be conducted in a wide pH range from 2.0 to 7.0. The maximum adsorption capacity of GA towards U(VI) at pH 4.0 and T = 298 K was 238.67 mg/g calculated from the Langmuir model. The GA had greatly rapid adsorption property for the removal of U(VI) at pH 4.0. Kinetic data showed good correlation with pseudo-second-order equation. Fourier transform infrared spectroscopy and X-ray photoelectron spectrometry characterizations showed that GA adsorbed U(VI) through chemical interaction by oxygen-containing and nitrogen-containing groups functional groups. The results show that GA has excellent application potential as an adsorbent material for removing U(VI) from aqueous solution. Graphical abstract: An ultra-light graphene aerogel (GA) has been facilely prepared and used for U(VI) removal. Image 1 Highlights: An ultra-light graphene aerogel (GA) has been facilely prepared. The GA exhibited a high adsorption capacity for U(VI) in a wide pH range of 2.0–7.0. The GA exhibited greatly rapid adsorption and easily separation property. The maximum adsorption capacity of U(VI) on GA at pH 4.0 was 238.67 mg/g.